Notes on the Mass Occurrence of the Ciliate Mesodinium rubrum (non-toxic red tide) in Malacca River, Malaysia - Pau, Suriyanti Su Nyun; Nasir, Dzulhelmi Muhammad; Usup, Gires (JURNAL BIOLOGI INDONESIA, 2017)
SHORT COMMUNICATION